Examining the role of grape seed extract in enhancing collagen crosslinking and its effect on the shear bond strength of Universal adhesive to contaminated dentine (Mustansiria Dental Journal, 2025)
Aim: The purpose of this study is to evaluate the effect of a collagen cross-linker, grape seed extract (GSE), applied at different times (1, 3, and 5 minutes) on the shear bond strength (SBS) of a universal adhesive bonding system applied to dentine after contamination with blood or blood and hemostatic agent (HA). Materials and Methods: Seventy-two teeth were divided into three main groups. Group A, the control group, (n=8) treated with only Scotchbond Universal. The remaining teeth were divided into two experimental groups, (n=32) for each according to the type of contamination. Group B was contaminated with blood, while Group C was contaminated with both blood and HA. Each contamination group was further divided into four subgroups based on the timing of GSE application. One subgroup did not receive any GSE application, while the other three subgroups had application of GSE for 1, 3, and 5 minutes. Then experimental groups had adhesive application as in group A, after adhesive application and composite resin placement. SBS was measured using a universal testing machine. Results: Groups that had GSE had nosinificant difference with control (p